2022
DOI: 10.48550/arxiv.2206.12315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Augmented unprojected Krylov subspace methods from an alternative view of an existing framework

Abstract: Augmented Krylov subspace methods aid in accelerating the convergence of a standard Krylov subspace method by including additional vectors in the search space. These methods are commonly used in High-Performance Computing (HPC) applications to considerably reduce the number of matrix vector products required when building a basis for the Krylov subspace. In a recent survey on subspace recycling iterative methods [Soodhalter et al, GAMM-Mitt. 2020], a framework was presented which describes a wide class of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The proof of this equivalence is a trivial extension of the proof shown in [5] to the shifted case and is thus not repeated here. We now propose to solve the unprojected problem using the unprojected, shift-invariant Krylov subspace K j (A, b).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The proof of this equivalence is a trivial extension of the proof shown in [5] to the shifted case and is thus not repeated here. We now propose to solve the unprojected problem using the unprojected, shift-invariant Krylov subspace K j (A, b).…”
mentioning
confidence: 94%
“…One way to overcome this difficulty is to use the observation made in [5] where it was shown that the projected problem (5.3) has an unprojected equivalent given by Find t j (σ) ∈ V j as an approximate solution corresponding to shift σ for the shifted linear system (σI…”
mentioning
confidence: 99%
See 1 more Smart Citation